The metaphysics of paradox : Jainism, absolute relativity, and religious pluralism - Schwartz, Wm. Andrew (Explorations in Indic traditions: theological, ethical, and philosophical., 2018)
This book offers a new paradigm for religious pluralism by exploring Indic insights of Jainism and the nature of paradox.